ANALISIS PENYERAPAN PANAS PADA COVER ACCU DI MOBIL SUV - Faizal, Mohamad; Fitri, Mariza (Bina Teknika, 2016)
Batteries or accumulators on the car serves to store electrical energy in the form of chemical energy, which will be used to supply the system to the electric starter, ignition system, lights and other electrical components. In the car, the battery damage can occur due to many factors including temperature. Batteries that work at higher temperatures will have a life span that is lower than at normal room temperature (25OC). Generally, the location of the battery is in the engine room so that the battery position was close to the engine. The car engine works at the optimum temperature 80 ° C - 90 ° C so that the heat is around the engine room can be exposed directly to the battery and can affect the performance and lifetime of the battery. Adding insulation on cover, with low thermal conductivity coefficient will decrease heat transfer rate . Polyurethane as insulation with 7,5 mm thickness will maintenance battery liquid temperature 45,5 OC after running through three hundred minutes.